Quantifying the sources of ionosphere day‐to‐day variability - Matsuo, Tomoko (2019)
Simulations from the coupled Whole Atmosphere Model and Global Ionosphere Plasmasphere show significant day‐to‐day variations in total electron content (TEC) and the F region peak density (NmF2). The Whole Atmosphere Model‐Global Ionosphere Plasmasphere was driven by the auroral precipitation patterns inferred from TIROS/NOAA, daily solar irradiance measurements derived from the satellite observations, and 5‐min interplanetary magnetic field/solar wind parameters during June and July 2012. Overall, the combination of solar, magnetosphere, and lower atmosphere drivers produced similar magnitude of variability consistent with that seen in observations. Results also show that the relative variability is much larger at night than in the daytime, due to much lower background density, and depended strongly on latitude and local time. Additional simulations were also performed to distinguish the contributions to the variability from solar activity, geomagnetic activity, and lower atmospheric perturbations. Results show that globally, geomagnetic activity is the main contributor to the NmF2 variability, followed by lower atmosphere perturbation, and then solar activity. For TEC variability, again, geomagnetic activity is the main contributor, followed by solar activity, and then lower atmosphere perturbation. In terms of absolute variability, at low latitudes solar activity dominates the TEC variability, most likely due to the importance of solar EUV driving the changes in ionosphere density through photoionization, while the contributions from the lower atmosphere and geomagnetic activity are almost equally. For the middle‐ and high‐latitude regions, the solar activity and geomagnetic activity are the most important sources for the TEC variability.